Kajian keamanan pangan dan tingkat prevalensi cemaran bakterisusu di Sentra Pengembangan Sapi Perah Cilongok - Afduha Nurus Syamsi; Triana Yuni Astuti; Hermawan Setyo Widodo (Faculty of Animal Science, Universitas Brawijaya, 2018)
The experiment was aimed to assess the food securitythrough physical properties, chemical composition and prevalence rate of milk bacterial contamination in Cilongok dairy cattle development center. Surveys and observations were conducted to obtain data on milking and milk processing applied by farmer and to obtain data on physical properties, chemical composition, and milk total bacterial count. The materialswere used farmer and milk samples taken 20 liters in total from 13 Andini Lestari 1 farmers and 7 Andini Lestrari 2 farmers. Data from the laboratory were analyzed descriptively based on the Standard Nasional Indonesia (SNI): 3141.1.2011,